First Description of a Helicopter-Borne ECPR Team for Remote Refractory Out-of-Hospital Cardiac Arrest. (2nd January 2022) - Hutin, A.; Ricard-Hibon, A.; Briole, N.; Dupin, A.; Dagron, C.; Raphalen, J. H.; Mungur, A.; An, K.; Carli, P.; Lamhaut, L.
Abstract: Introduction: Access time to extracorporeal cardiopulmonary resuscitation (ECPR) refractory out of hospital cardiac arrest (OHCA) is a crucial factor. In our region, some patients are not eligible to this treatment due to the impossibility to reach the hospital with reasonable delay (ideally 60 min). In order to increase accessibility for patients far from ECPR centers, we developed a helicopter-borne ECPR-team which is sent out to the patient for ECPR implementation on the scene of the OHCA. Methods: We conducted a retrospective monocentric study to evaluate this strategy. The team is triggered by the local emergency medical service and heliborne on the site of the OHCA. All consecutive patients implemented with ECPR by our heliborne ECPR team from January 2014 to December 2017 were included. We analyzed usual CA characteristics, different times (no-flow, low-flow, time between OHCA and dispatch…), and patient outcome. Results: During this 4-year study period, 33 patients were included. Mean age was 43.9 years. Mean distance from the ECPR-team base to OHCA location was 41 km. Mean low-flow time was 110 minutes. Five patients survived with good neurological outcome; 6 patients developed brain death and became organ donors. Conclusion: These results show the possibility to make ECPR accessible for patients far from ECPR centers. Survival rate is non negligible, especially in the absence of therapeutic alternative. An earlier trigger of the ECPR-team could reduce the low-flow time and probably increase survival. This strategy improves equity of access to ECPR and needs to be confirmed by further studies.